2017
DOI: 10.1016/j.cca.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Perspective and priorities for improvement of parathyroid hormone (PTH) measurement – A view from the IFCC Working Group for PTH

Abstract: Parathyroid hormone (PTH) measurement in serum or plasma is a necessary tool for the exploration of calcium/phosphate disorders, and is widely used as a surrogate marker to assess skeletal and mineral disorders associated with chronic kidney disease (CKD), referred to as CKD-bone mineral disorders (CKD-MBD). CKD currently affects >10% of the adult population in the United States and represents a major health issue worldwide. Disturbances in mineral metabolism and fractures in CKD patients are associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…Studies of VK-4 supplementation into women under hormone replacement therapy, carried out by Ishida and Kawai [24] have shown significant improvement of BMD parallel to raise into osteocalcin in serum. Also, the same study have shown a decrease into number of fractures in such women [24][25][26]. These data corroborate our experiments were carried in a mouse model.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Studies of VK-4 supplementation into women under hormone replacement therapy, carried out by Ishida and Kawai [24] have shown significant improvement of BMD parallel to raise into osteocalcin in serum. Also, the same study have shown a decrease into number of fractures in such women [24][25][26]. These data corroborate our experiments were carried in a mouse model.…”
Section: Discussionsupporting
confidence: 81%
“…to be used to reduce bone loss in women with osteoporosis [26][27][28]. In this paper we showed that OVX led to significant decreased in BMD.…”
Section: Figurementioning
confidence: 72%
“…A significant variation can be seen when the same sample is measured with different i‐PTH assay kits using different readout systems. Although the results of different i‐PTH assays generally correlate well with each other, there was significant discrepancy between the i‐PTH assays in i‐PTH concentrations in CKD patients .…”
Section: Clinical Usefulness and Problems Of Pth Assays In Managementmentioning
confidence: 86%
“…This complexity, in turn, can hinder our current understanding of whether one, several or all forms of a measurand are of clinical interest. Of the many examples, human chorionic gonadotropin (HCG) [5], troponin [56] and PTH [69] represent paradigmatic and commonly requested laboratory measurands. In the last few years, the increased awareness of the lack of clearly defined measurands, reference methods and/or reference materials for many measurands of absolute clinical value has prompted further efforts to achieve harmonization, particularly as the final goal is to assure the comparability not only of analytical results but also of the ultimate laboratory information and not only in clinical chemistry but also in all fields of laboratory medicine.…”
Section: Discussionmentioning
confidence: 99%